Estimation of the Yield of Some Rainfed Crops in the Present Irrigated Lands of Iran - Safora Jafarnodeh; Afshin Soltani; Ramtin Joolaie; Shahrzad Mirkarimi; Ebrahim zeinali (بوم شناسی کشاورزی, 2023)
Introduction Occurrence of drought and reduction of rainfall in the future will limit the cultivation of irrigated crops. Thus, it is probable that a part of the present irrigated lands and orchards of Iran may be unavailable for the cultivation of irrigated crops, but it is possible to cultivate rainfed crops in these lands. However, the available potential for cultivation of rainfed crops with respect to the soil type, climate and other factors is not known. Limited water resources, on the one hand, and the growing population along with increasing the need to produce food, on the other, make it necessary to have a comprehensive, practical and accurate program. Therefore, research on this issue is essential. In this study, production potential of rainfed wheat (Triticum aestivum), barley  (Hordeum vulgare L.), chickpea (Cicer arietinum L.), lentil (Lens culinaris Medik) and canola (Brassica napus)  in irrigated lands (fields and orchards) was modeled.Materials and Methods  Weather stations (position and distribution), long-term weather data (15 to 30 years), HC27 soil map, crop management data plant parameters were used to determine the yield in this study using SSM-iCrop2 model. In each zone, the yield was determined and compared with the actual data. In other words, the model output were compared with the actual current rainfed yields of each province and then it was determined that whether the model precision was sufficient for this study. Other calculations (determining the average yield of provinces) and generation of maps were done using ArcGIS V.10.2. The yield obtained by farmers in these lands was considered as 50 and 70 percent of yield potential. Also, the yields were categorized into four classes of excellent, good, medium and non-suitable. This classification is based on economic- agronomic profit of crop harvest.Results and Discussion The results of this study showed that the conditions of rainfed production in each province of the country is suitable/appropriate for some crops and unsuitable/inappropriate for some other. In case the yield of farmers reached 70 percent of yield potential by optimum management, all provinces will be classified into the upper average group (3, 18 and 10 provinces in excellent, good and medium groups) for wheat. For barley 30 (3, 10 and 17 provinces in excellent, good and medium groups), for chickpea 30 (3, 6 and 21 provinces in excellent, good and medium groups), for lentil 31 (13 and 18 and 10 provinces in good and medium groups) and for canola 30 (4, 5 and 21 provinces in excellent, good and medium groups) provinces will be placed in the upper average group. Based on 70 percent of yield potential of canola, barley and chickpea, only on province is placed in non-suitable group. On the other hand, in case the yield of farmers reaches 50 percent of yield potential due to improper management, for wheat 30 (2, 2 and 26 provinces in excellent, good and medium groups), for barley 28 (4 and 24 provinces in good and medium groups), for chickpea 18 (4 and 14 provinces in good and medium groups), for lentil 28 (3 and 10 provinces in good and medium groups) and for canola 25 (5 and 20 provinces in good and medium groups) will be classified into the upper average group. Based on 50 percent of yield potential of rainfed wheat, barley, canola, chickpea and lentil, 1, 3, 6, 13 and 3 provinces were placed in non-suitable group, respectively.Conclusion According to the results of this study, a major part of the provinces will be placed in medium and non-suitable groups in case of improper management, and agricultural productions will not satisfy the needs of the country. Therefore, it is necessary to pay a special attention to agronomic management of rainfed crops, as the agricultural production of the country will not be acceptable unless 70 percent of yield potential is achieved.